THE EFFECT OF SAFETY TRAINING AND WORKPLACE ATTITUDES ON WORKPLACE SAFETY ON ONLINE OJEK DRIVERS PT. APLIKASI KARYA ANAK BANGSA WHICH OPERATING IN THE TAMBUN SELATAN DISTRICT AREA - Tungga Buana Irfana; Mahesha Ananda Wiguna; Tungga Buana Diana (Jurnal Ekonomi, 2023)
Study This aim know the effect of safety training and workplace attitudes on security in place work for online motorcycle taxi drivers operating in the sub-district area South Tambun at PT. Aplikasi Karya Anak Bangsa (Go-Jek). Method analysis used in study This is with method analysis multiple linear regression . Population used in study This are 80 online motorcycle taxi drivers PT. Aplikasi Work Nation (Go-Jek) and with a sample of 80 people using saturated sampling method , ie technique taking sample when all member population used as sample . Data processing techniques using partial test method (t-test) and significant test simultaneously (f-test). Results obtained in study This show that in a manner partial Safety Training and Workplace Attitudes effect positive , in partial Workplace Attitudes and Security In place Work influential positive , and that safety training and workplace attitudes are simultaneous own influence positive and significant to security in place work .